Huacas of the National University of Engineering and the true Huaca Aliaga - Guzmán García, Enrique (2015)
This article starts with an account of the archaeological remains in the area of the campus of the National University of Engineering (UNI), in Lima-Perú, and its surroundings. Most of the remains are temporarily placed in the Late Intermediate Period (1100-1440 A.D.) and Inca Period (1440-1532 A.D.). The first site to be analyzed, also the most important, is the famous huaca Aliaga (today destroyed); its true location is specified, which was outside the current campus. Then the article investigates the huaca El Carmen, in the Human Settlement Villa El Carmen, neighbor to the University. Subsequentis the inquiry regarding the remains that once were within the campus, as the ritual mound that was located in the place of today’s Faculty of Architecture and Urbanism Arts (FAUA), and those still within the existing campus: the UNI-CISMID huaca (misnamed Aliaga) and the UNI-MINAS huaca. The article presents a general historical reconstruction that reviews its pre-Hispanic, colonial and republican occupation, and the current situation of both. Suggestions are made regarding its value assessment, also showing successful contemporary attempts, both in Peru and abroad, that include historical remains.